Qard Alhassan Institution as A Sustainable Ethical Financing Solution for MiddleClass Individuals in Muslim Majority Countries - Al-Aidaros, Al-Hasan Muhammad (UUM Press, 2023)
The purpose of this study is to propose a Qard Alhassan institution based on a Quranic concept regarding financing and borrowing. It is whereby a certain group of society is assisted, specifically middle-class individuals, that helps them get the finance they need and to return what they borrowed without any interest, while preserving the capital of the lenders who will receive the Hereafter reward, but the institution goal is not striving for profits though it may impose minimal fees for its services. The study used a qualitative approach. A holistic review of the Quranic verses, that mention several financial issues such as Riba, Qard alhassan, the study concludes that there is an urgent need to integrate the elements of Iman (believe in Allah) and Akhlaq (Islamic ethics) into the Islamic finance equation. In order to find out the obstacles that may face Qard Alhassan institution, the study presented and analyzed the case of the Malaysian Hajj Corporation project (known as Lembaga Tabung Haji), as there are elements of similarity with the proposed institution. In addition, over 100 personal interviews conducted, in two stages, with Malaysian and Arab experts in the academic and professional aspects in the Islamic financial and banking sector. The interviews conducted in span of 5 years (from 2018 to the end of 2022). The study has proposed a new Islamic financing project that represents the idea of Qard Alhassan institution, provided that several elements to be implemented as mentioned in the study’s recommendations.